Time-Domain Characterization of Photonic Integrated Filters Subject to Fabrication Variations - Ye, Yinghao; Wang, Mi; Spina, Domenico; Bogaerts, Wim; Dhaene, Tom (Journal of lightwave technology, 2019)
Fabrication variations are a key factor to degrade the performance of photonic integrated circuits (PICs), and especially wavelength filters. We propose an efficient modeling approach to quantify the effects of fabrication variations on the time-domain performance of linear passive photonic integrated circuits (including the wavelength filters) in the design stage, before fabrication. In particular, this novel approach conjugates the accuracy of the Polynomial Chaos (PC) expansion in describing stochastic variations and the efficiency of a Vector Fitting (VF)-based baseband modeling technique in performing time-domain simulations. A suitable example validates the performance of the proposed method.